Reaching across from here to there, in precarious times: Remote-teaching embodied creative practice through scores, instructions, and poetic invitations - Longley, Alys; Moraes, Janaína; Cook, Joanna (Critical Studies in Teaching and Learning, 2023)
How can we attend to students’ experience of agency, spatiality, sensation, mobility, freedom, and play in tertiary dance and interdisciplinary arts education, while working through lockdowns or in readiness for them? How do we cultivate care, joy, and imagination in such teaching-learning situations? How do we create spaces that are grounded and focussed while also creating maximum space for independence, idiosyncrasy, experimentation, delight in material practice and difference? This article responds to the above question through ten vignettes narrated by Alys – a Masters and PhD supervisor and Course Director teaching undergraduate courses, Janaína and Joanna – post graduate students and teaching assistants on the same courses. Concepts of weak theory, articulated by Biesta (2009) and Kosofsky Sedgwick (1993), and the poetics of care (Tronto, 1998) are core to this article, which posits that as educators our commitment to wellbeing and our acts of care are of utmost importance in precarious times.